Preparation method and application of graphene-coated tin disulfide nanomaterial

The preparation of graphene-coated tin disulfide nanomaterials through solvent method and freeze-drying method, solving the problem of volume change and capacity attenuation of lithium-ion battery negative electrode materials during circulation, and achieving high energy density and long cycle stability electrode materials performance.

CN118851251BActive Publication Date: 2025-01-07QILU INST OF TECH

Patent Information

Application Number
CN202411339780.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2025-01-07
Estimated Expiration
2044-09-25

AI Technical Summary

Technical Problem

The existing lithium-ion battery negative electrode materials have large volume changes and fast capacity decay during the charge and discharge cycle, which is difficult to meet the needs of high energy density and long cycle stability, especially the problem of rapid attenuation of specific capacity after multiple cycles of tin disulfide materials.

Method used

The solvent-based chemical reaction-assisted freeze-drying method was used to prepare graphene oxide-coated tin oxide nanoparticles, and then calcined and vulcanized under the protection of inert gas to obtain graphene-coated ultrafine tin disulfide nanoparticles (SnS2/RGO) composite material , through this method, the volume expansion of SnS2 is effectively alleviated and the conductivity and rate performance of the electrode material are improved.

Benefits of technology

The prepared SnS2/RGO composite material exhibits high charge and discharge specific capacity, excellent rate performance and long cycle stability of large-magnification. It can cycle stably for 250 cycles at a current density of 1.0 A g-1, and the capacity remains 974.5 mA h g-1. , and provides a stable discharge specific capacity at a current density of 0.2-10.0 A g-1. The reversible specific capacity reaches 943.3 mA h g-1 after the current density is restored.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118851251B_ABST
    Figure CN118851251B_ABST
Patent Text Reader

Abstract

The present invention discloses a preparation method and application of a graphene-coated tin disulfide nanomaterial, belonging to the technical field of negative electrode materials for lithium-ion batteries. The graphene-coated tin disulfide nanomaterial is prepared by the following method: dispersing graphene oxide in anhydrous ethylenediamine, then adding tin salt and ultrasonically dispersing to obtain a dispersion; adding NaOH solution dropwise to the dispersion, stirring to react, centrifuging, washing, and freeze-drying the reactant to obtain Sn6O4(OH)4 / GO; and calcining Sn6O4(OH)4 / GO and sublimated sulfur at high temperature under an inert atmosphere to obtain SnS2 / RGO. The present invention adopts an efficient and fast preparation method to prepare graphene-coated tin disulfide nanomaterials, and the prepared material particles are evenly distributed and completely coated with graphene, and have excellent rate performance and long cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of negative electrode materials for lithium-ion batteries, and in particular to a preparation method and application of a graphene-coated tin disulfide nanomaterial. Background Art

[0002] As the mainstream product of secondary batteries, lithium-ion batteries (LIBs) have significantly reduced the world's dependence on fossil fuels. Their widespread application has profoundly changed the way people live and made outstanding contributions to promoting green and sustainable development. However, in the face of the growing demand for high energy density, current graphite-based anode materials (whose theoretical capacity is only 372 mAh g -1 The limitations of Sn-based sulfide electrode materials have become increasingly prominent and urgently need to be broken through. Sn-based sulfide electrode materials have become a hot topic of research due to their excellent energy storage potential, but the large volume change and rapid capacity decay of this electrode material during the charge and discharge cycle have hindered its transition from laboratory to large-scale application.

[0003] Tin disulfide materials have a high theoretical specific capacity (1231 mAh g -1 ), is expected to be used as a negative electrode material for lithium-ion batteries to meet the energy storage devices with increasingly higher energy density requirements. However, tin disulfide materials, like other Sn-based materials, also have the problem of rapid attenuation of specific capacity after multiple cycles. Patent CN106654192A discloses a tin sulfide / graphene sodium-ion battery composite negative electrode material and a preparation method thereof. The tin sulfide / graphene composite material obtained by freeze-drying and calcination with commercial tin sulfide as a precursor has a large particle size (about 50 nm) and is unevenly distributed. Patent CN107134574A discloses a method for preparing a 3D honeycomb reduced graphene oxide tin disulfide composite, but the prepared 3D RGO / SnS2 electrode material has a low conductivity at 0.1 A g -1 The current density can only be stably cycled for 50 cycles; in the rate performance test, at 1.0 A g -1 At the current density, the capacity can only be maintained at 450.0 mA hg -1 The RGO-SnS2 electrode material reported in the literature "Preparation and lithium storage performance of graphene-loaded tin-based materials and molybdenum-based materials. Chen Peng. 2013. Shanghai University" is 0.66 A g -1 The current density can only be stably cycled for 40 cycles. In the rate performance test, at 3.3 A g -1 At this current density, the capacity can only be maintained at 466.0 mA h g -1 Therefore, how to design and prepare SnS2-based electrode materials with both high rate and long-term cycle performance remains to be explored. Summary of the invention

[0004] In view of the above-mentioned prior art, the purpose of the present invention is to provide a method for preparing a graphene-coated tin disulfide nanomaterial and its application. The present invention adopts a simple solvent-based chemical reaction-assisted freeze-drying method to prepare a graphene oxide-coated tin oxide nanoparticle (Sn6O4(OH)4 / GO) composite material, and then uses sublimated sulfur as a sulfur source, under the protection of an inert gas, to calcine and sulfurize the composite material obtained above to prepare a graphene-coated ultrafine tin disulfide nanoparticle (SnS2 / RGO) composite material. The nanomaterial with a graphene-coated structure and synergistic sulfurization modification prepared by this method can effectively alleviate the volume expansion of SnS2 when applied to the negative electrode of a lithium-ion battery, improve the conductivity of the electrode material, and exhibit high charge and discharge specific capacity, excellent rate performance, and high rate long cycle stability.

[0005] To achieve the above object, the present invention adopts the following technical solution:

[0006] In a first aspect of the present invention, a graphene-coated tin disulfide nanomaterial is provided, which is prepared by the following method:

[0007] (1) dispersing graphene oxide in anhydrous ethylenediamine, then adding tin salt and ultrasonically dispersing to obtain a dispersion;

[0008] (2) Adding NaOH solution dropwise to the dispersion, stirring to react, centrifuging, washing, and freeze-drying the reactant to obtain Sn6O4(OH)4 / GO;

[0009] (3) Sn6O4(OH)4 / GO and sublimed sulfur are calcined at high temperature under an inert atmosphere to obtain SnS2 / RGO.

[0010] Preferably, in step (1), the ratio of the added amounts of graphene oxide, anhydrous ethylenediamine and tin salt is (30-50) mg: (20-40) mL: (200-500) mg.

[0011] Preferably, in step (1), the tin salt is one or more of SnCl4•5H2O, SnCl2•2H2O.

[0012] Preferably, the concentration of the NaOH solution is 0.12-0.15 mol / L, and the volume ratio of the NaOH solution to anhydrous ethylenediamine is (0.5-1.5): (0.5-1.5).

[0013] Preferably, in step (2), the reaction time is 40-100 min.

[0014] Preferably, in step (2), during washing, water and ethanol are used alternately to wash and separate the precipitate; during centrifugation, the centrifuge speed is 5500-8500 rpm.

[0015] Preferably, the freeze-drying temperature is -80°C and the time is 12 hours.

[0016] Preferably, in step (3), the mass ratio of Sn6O4(OH)4 / GO to sublimated sulfur is 1:(1-3).

[0017] Preferably, in step (3), the high temperature calcination conditions are: heating to 400-600°C at a heating rate of 2-5°C / min, and maintaining the temperature for calcination for 0.5-1.5h.

[0018] Preferably, the inert atmosphere is an argon atmosphere or a nitrogen atmosphere.

[0019] Preferably, in step (1), the graphene oxide is prepared by the following method:

[0020] Graphite powder, sulfuric acid with a mass concentration of 98% and sodium nitrate are ultrasonically dispersed uniformly to obtain a mixture; potassium permanganate is added to the mixture, stirred uniformly, and then deionized water and 30% hydrogen peroxide are added dropwise, followed by stirring for 50-70 hours. The obtained brown mixture is washed and centrifuged to obtain graphene oxide.

[0021] Preferably, the ratio of the added amounts of graphite powder, concentrated sulfuric acid, sodium nitrate, potassium permanganate, deionized water and hydrogen peroxide is: (4-6) g: (100-140) ml: (2-3) g: (10-20) g: (100-200) ml: (25-75) ml.

[0022] Preferably, during washing, deionized water (H2O) is used to wash until the pH value reaches 7±0.5; during centrifugation, the speed of the centrifuge is 8500-11000 rpm.

[0023] The second aspect of the present invention provides the use of the above-mentioned graphene-coated tin disulfide nanomaterial in the preparation of lithium-ion battery negative electrode materials.

[0024] Beneficial effects of the present invention:

[0025] 1. The present invention adopts an efficient and fast preparation method to prepare graphene-coated tin disulfide nanomaterials, and obtains SnS2 / RGO composite materials with ultrafine nanoparticles modified in structure (particle size is 2-5 nm). The prepared material particles are evenly distributed and completely coated with graphene. However, the tin sulfide / graphene composite materials reported previously, which are obtained by freeze-drying and calcining commercial tin sulfide as a precursor, have larger particle sizes (about 50 nm) and are unevenly distributed.

[0026] 2. The SnS2 / RGO composite material obtained by the present invention has excellent rate performance and long cycle performance.-1 The current density can be stably cycled for 250 cycles, and the capacity can still be maintained at 974.5 mA h g -1 , while the existing reported 3D RGO / SnS2 electrode materials have a -1 The current density can only be stably cycled for 50 cycles, and the capacity is only close to 800.0 mA h g -1 In the rate performance test, the SnS2 / RGO electrode material prepared by the present invention has a high rate performance of 0.2-10.0 A g -1 The current densities were 936.1, 773.6, 714.9, 648.6, 539.9 and 429.7 mA h g -1 The discharge capacity is restored to 0.2 A g -1 After 105 cycles, the reversible specific capacity can reach 943.3 mA h g -1 The reported 3D RGO / SnS2 electrode material has a high rate performance at 1.0 A g -1 At the current density, the capacity can only be maintained at 450.0 mA hg -1 about.

[0027] 3. The present invention has an advanced design concept. It utilizes the heat release characteristic of anhydrous ethylenediamine when it meets water to innovatively design and prepare a Sn6O4(OH)4 / GO composite material with a coating structure. This is used as a precursor for sulfurization modification, which can achieve particle nano-modification, and the particle size reaches about 2-5 nm, which greatly increases the active sites of the electrode material. At the same time, it can effectively alleviate the volume expansion of the electrode material during energy storage, enhance the structural stability of the electrode material, and cooperate with the three-dimensional graphene coating structure to greatly improve the energy storage performance of the electrode material, which is expected to achieve a high-rate and long cycle life for lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 : XRD patterns of Sn6O4(OH)4 / GO, SnS2 / RGO prepared in Example 1 and SnO2 / RGO nanocomposites prepared in Comparative Example 1;

[0029] Figure 2 : Microstructure and structure of Sn6O4(OH)4 / GO, SnS2 / RGO and SnO2 / RGO nanocomposites prepared in Example 1; wherein (a) is the SEM morphology of Sn6O4(OH)4 / GO; (b) is the SEM morphology of SnO2 / RGO; (c) is the SEM morphology of SnS2 / RGO; (d) is the HRTEM image of SnS2 / RGO;

[0030] Figure 3: Nitrogen adsorption-desorption curves and pore size distribution curves of the SnS2 / RGO composite material prepared in Example 1 and the SnO2 / RGO composite material prepared in Comparative Example 1; wherein (a) is the nitrogen adsorption-desorption curve; (b) is the pore size distribution curve;

[0031] Figure 4 : High-resolution XPS spectrum of the SnS2 / RGO composite material prepared in Example 1; wherein (a) is the high-resolution XPS spectrum of Sn3d; (b) is the high-resolution XPS spectrum of S2p; (c) is the high-resolution XPS spectrum of N1s; (d) is the high-resolution XPS spectrum of C1s;

[0032] Figure 5 : The SnS2 / RGO composite material prepared in Example 1 has a -1 and 2.0 A g -1 Cycling performance diagram under current density;

[0033] Figure 6 : Rate performance diagram of SnO2 / RGO composite materials prepared in Comparative Example 1 and SnS2 / RGO composite materials prepared in Example 1;

[0034] Figure 7 : Long cycle performance diagram of SnS2 / RGO composite material prepared in Example 1. DETAILED DESCRIPTION

[0035] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.

[0036] In order to enable those skilled in the art to more clearly understand the technical solution of the present application, the technical solution of the present application will be described in detail below in conjunction with specific embodiments.

[0037] The test materials used in the examples of the present invention are all conventional test materials in the art and can be purchased through commercial channels.

[0038] Example 1: Preparation of SnS2 / RGO composite material:

[0039] (1) Preparation of graphene oxide:

[0040] 5 g of graphite powder was added into a round-bottom flask containing 120 ml of 98% concentrated sulfuric acid and 2.5 g of sodium nitrate, and the mixture was stirred and evenly mixed, and then ultrasonically dispersed for 30 min to obtain a mixture;

[0041] After stirring for a while, 15 g of potassium permanganate was slowly added to the mixture, and the mixture was stirred for 24 h to be evenly dispersed. Then, 150 ml of deionized water and 50 ml of 30% hydrogen peroxide were added dropwise in an ice-water bath, and then mechanically stirred for 60 h.

[0042] The brown mixture was then washed with deionized water for several times until the pH value was close to 7, and the target product, graphene oxide (GO), was obtained by centrifugation at 8000 rpm for 3 min.

[0043] (2) Preparation of Sn6O4(OH)4 / GO:

[0044] 40 mg of the GO prepared above was dispersed in 30 mL of anhydrous ethylenediamine solution and ultrasonically dispersed for 30 min, and then 0.45 g of SnCl2•2H2O was added and ultrasonically dispersed for 20 min to obtain a dispersion;

[0045] 30 mL of 0.12 mol / L NaOH solution was added dropwise to the dispersion, and the mixture was stirred for reaction for 1 h. The obtained reactant was centrifuged at 6000 rpm for 5 min, and the precipitate was washed and separated by alternating water and ethanol for multiple times, and freeze-dried at -80 °C for 12 h to obtain the product Sn6O4(OH)4 / GO.

[0046] (3) Preparation of SnS2 / RGO:

[0047] Take 0.16 g of the prepared Sn6O4(OH)4 / GO and 0.32 g of sublimated sulfur, place the two samples at two different positions on an alumina porcelain boat, place the porcelain boat in a tube furnace, and heat the mixture to 550°C at a heating rate of 5°C / min under an argon atmosphere. Calcine at 550°C for 1 h and cool naturally to room temperature to obtain SnS2 / RGO.

[0048] Example 2: Preparation of SnS2 / RGO composite material:

[0049] (1) Preparation of graphene oxide:

[0050] 4 g of graphite powder was added into a round-bottom flask containing 100 ml of 98% concentrated sulfuric acid and 2 g of sodium nitrate, and the mixture was stirred and evenly mixed, and then ultrasonically dispersed for 30 min to obtain a mixture;

[0051] After stirring for a while, 10 g of potassium permanganate was slowly added to the mixture, and the mixture was stirred for 24 h to be evenly dispersed. Then, 100 ml of deionized water and 25 ml of 30% hydrogen peroxide were added dropwise in an ice water bath, and then mechanically stirred for 60 h.

[0052] The brown mixture was then washed with deionized water for several times until the pH value was close to 7, and the target product, graphene oxide (GO), was obtained by centrifugation at 8000 rpm for 3 min.

[0053] (2) Preparation of Sn6O4(OH)4 / GO:

[0054] 30 mg of the GO prepared above was dispersed in 20 mL of anhydrous ethylenediamine solution and ultrasonically dispersed for 30 min, and then 0.20 g of SnCl2•2H2O was added and ultrasonically dispersed for 20 min to obtain a dispersion;

[0055] 20 mL of 0.135 mol / L NaOH solution was added dropwise to the dispersion, and the mixture was stirred for reaction for 1 h. The obtained reactant was centrifuged at 6000 rpm for 5 min, and the precipitate was washed and separated by alternating water and ethanol for multiple times, and freeze-dried at -80 °C for 12 h to obtain the product Sn6O4(OH)4 / GO.

[0056] (3) Preparation of SnS2 / RGO:

[0057] Take 0.16 g of the prepared Sn6O4(OH)4 / GO and 0.16 g of sublimated sulfur, place the two samples at two different positions on an alumina porcelain boat, place the porcelain boat in a tube furnace, and heat the mixture to 550°C at a heating rate of 5°C / min under an argon atmosphere. Calcine at 550°C for 1 h and cool naturally to room temperature to obtain SnS2 / RGO.

[0058] Example 3: Preparation of SnS2 / RGO composite material:

[0059] (1) Preparation of graphene oxide:

[0060] 6 g of graphite powder was added into a round-bottom flask containing 140 ml of 98% concentrated sulfuric acid and 3 g of sodium nitrate, stirred and mixed evenly, and then ultrasonically dispersed for 30 min to obtain a uniform mixture;

[0061] After stirring for a while, 20 g of potassium permanganate was slowly added to the mixture, and the mixture was stirred for 24 h to be evenly dispersed. Then, 200 ml of deionized water and 50 ml of 30% hydrogen peroxide were added dropwise in an ice-water bath, and then mechanically stirred for 70 h.

[0062] The brown mixture was then washed with deionized water for several times until the pH value was close to 7, and the target product, graphene oxide (GO), was obtained by centrifugation at 8000 rpm for 3 min.

[0063] (2) Preparation of Sn6O4(OH)4 / GO:

[0064] 50 mg of the GO prepared above was dispersed in 40 mL of anhydrous ethylenediamine solution and ultrasonically dispersed for 30 min, and then 0.50 g of SnCl2•2H2O was added and ultrasonically dispersed for 20 min to obtain a dispersion;

[0065] 40 mL of 0.15 mol / L NaOH solution was added dropwise to the dispersion, and the mixture was stirred for reaction for 1 h. The obtained reactant was centrifuged at 6000 rpm for 5 min, and the precipitate was washed and separated by alternating water and ethanol for multiple times, and freeze-dried at -80 °C for 12 h to obtain the product Sn6O4(OH)4 / GO.

[0066] (3) Preparation of SnS2 / RGO:

[0067] Take 0.16 g of the prepared Sn6O4(OH)4 / GO and 0.48 g of sublimated sulfur, place the two samples at two different positions on an alumina porcelain boat, place the porcelain boat in a tube furnace, and heat the mixture to 550°C at a heating rate of 5°C / min under an argon atmosphere. Calcine at 550°C for 1 h and cool naturally to room temperature to obtain SnS2 / RGO.

[0068] Comparative Example 1: Preparation of SnO2 / RGO composite material:

[0069] (1) Preparation of graphene oxide:

[0070] 5 g of graphite powder was added into a round-bottom flask containing 120 ml of 98% concentrated sulfuric acid and 2.5 g of sodium nitrate, and the mixture was stirred and evenly mixed, and then ultrasonically dispersed for 30 min to obtain a mixture;

[0071] After stirring for a while, 15 g of potassium permanganate was slowly added to the mixture, and the mixture was stirred for 24 h to be evenly dispersed. Then, 150 ml of deionized water and 50 ml of 30% hydrogen peroxide were added dropwise in an ice-water bath, and then mechanically stirred for 60 h.

[0072] The brown mixture was then washed with deionized water for several times until the pH value was close to 7, and the target product, graphene oxide (GO), was obtained by centrifugation at 8000 rpm for 3 min.

[0073] (2) Preparation of Sn6O4(OH)4 / GO:

[0074] 40 mg of the GO prepared above was dispersed in 30 mL of anhydrous ethylenediamine solution and ultrasonically dispersed for 30 min, and then 0.45 g of SnCl2•2H2O was added and ultrasonically dispersed for 20 min to obtain a dispersion;

[0075] 30 mL of 0.12 mol / L NaOH solution was added dropwise to the dispersion, and the mixture was stirred for reaction for 1 h. The obtained reactant was centrifuged at 6000 rpm for 5 min, and the precipitate was washed and separated by alternating water and ethanol for multiple times, and freeze-dried at -80 °C for 12 h to obtain the product Sn6O4(OH)4 / GO.

[0076] (3) Preparation of SnO2 / RGO:

[0077] Take 0.16 g of the prepared Sn6O4(OH)4 / GO and place it in an alumina porcelain boat. Place the porcelain boat in a tube furnace and heat it to 550°C at a heating rate of 5°C / min under an argon atmosphere. Calcine at 550°C for 1 h and cool it naturally to room temperature to obtain SnO2 / RGO.

[0078] Test example:

[0079] 1. XRD analysis:

[0080] The XRD patterns of the Sn6O4(OH)4 / GO nanocomposite, SnS2 / RGO nanocomposite and SnO2 / RGO nanocomposite prepared in Example 1 and Comparative Example 1 were analyzed using a Bruker D8 Advance X-ray diffractometer (Cu target, λ=1.5406Å). Figure 1 ).

[0081] By comparing with the standard card, it can be found that the Sn6O4(OH)4 / GO nanocomposite material can be successfully converted into the SnS2 / RGO nanocomposite material through the preparation method of Example 1.

[0082] 2. Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) analysis:

[0083] The microstructure and structure of the Sn6O4(OH)4 / GO nanocomposite, SnS2 / RGO nanocomposite prepared in Example 1 and the SnO2 / RGO nanocomposite prepared in Comparative Example 1 were analyzed using a JEOL JSM-7800F field emission scanning electron microscope (SEM) and a JEOL JEM-2100plus transmission electron microscope (TEM).

[0084] The SEM image shows that the nanomaterial Sn6O4(OH)4 / GO prepared by solvent-based chemical reaction has different particle sizes, but is basically coated with graphene. The SnO2 / RGO nanocomposite obtained by calcination maintains the coated structure, but the particle size becomes larger and agglomeration occurs. On the contrary, the SnS2 / RGO nanocomposite prepared by sulfurization has a uniform particle size and is uniformly coated with graphene. The sulfurization treatment changes the size of the nanoparticles and forms abundant pores, which is conducive to the transmission of ions. The HRTEM image further shows that the diameter of the nanoparticles of the SnS2 / RGO composite material is about 2-5 nm. The test results show that the size of the nanomaterial can be reconstructed by sulfurization treatment, which is conducive to increasing the active sites of the electrode material, alleviating the volume expansion of the electrode material, and improving the structural stability of the electrode material, thereby improving the energy storage performance of the electrode material.

[0085] 3. Nitrogen adsorption, desorption and pore size test:

[0086] The SnS2 / RGO nanocomposite prepared in Example 1 and the SnO2 / RGO nanocomposite prepared in Comparative Example 1 were subjected to nitrogen adsorption and desorption and pore size distribution tests using a fully automatic physical adsorption instrument (BET) (model: American Mack ASAP 2460).

[0087] Depend on Figure 3 It can be seen that the test results show that both SnO2 / RGO and SnS2 / RGO composites have mesoporous characteristics, and SnS2 / RGO has a richer pore size distribution, which is conducive to the transmission of lithium ions.

[0088] 4. Sn3d, S2p, N1s and C1s XPS high-resolution spectrum analysis

[0089] The SnS2 / RGO composite material prepared in Example 1 was analyzed using a ThermoFisher ESCALAB 250 (aluminum target). The high-resolution spectrum of Sn 3d is shown in Figure 4a. The two peaks at 487.0 and 495.5 eV correspond to Sn 4+ Cationic Sn 3d 5 / 2 and Sn 3d 3 / 2 Four obvious characteristic peaks can be found in the S2p spectrum shown in Figure 4b, located at 162.0, 163.2, 165.4 and 169.4 eV, which are attributed to Sn-S (162.0 and 163.2 eV) and S covalent bonds (165.4 and 169.4 eV), respectively. Figure 4The results of Figures a and 4b indicate the successful synthesis of SnS2. For the N1s spectrum (Figure 4c), the three peaks at 398.8, 399.9, and 401.6 eV can be attributed to pyridinic N, pyrrolic N, and graphitic N, respectively, indicating that nitrogen was successfully introduced during the preparation of Sn6O4(OH)4 / GO during the solvent-based reaction. Figure 4 The C 1s spectrum in d is decomposed into three peaks, which are attributed to C=C (284.8 eV), CO (286.2 eV) and C-Cl (289.1 eV), indicating that the prepared SnS2 is successfully composited with graphene.

[0090] 5. Electrochemical performance test

[0091] The electrode slurry was mixed by dropping an appropriate amount of N-methyl-2-pyrrolidine (NMP) solvent to mix 80% of the active material (SnS2 / RGO prepared in Example 1 or SnO2 / RGO prepared in Comparative Example 1), 10% of acetylene black and 10% of polyvinylidene fluoride, so that the slurry could just flow. The mixed slurry was evenly coated on the copper foil cleaned with alcohol using an applicator, and after pre-drying, it was vacuum dried in a vacuum oven at 110°C for 12h. The electrolyte used was 1M LiPF6, where EC:DMC:EMC (1:1:1, wt%), containing 2.0% FEC. Then a polypropylene film (Celgard 2320) was used as a separator, and a pure lithium metal sheet was used as a counter electrode. The 2032-type button cell was assembled in a glove box filled with Ar atmosphere (oxygen and moisture less than 1 ppm), using metal shrapnel and gaskets. The charge and discharge test was carried out using a NEWARE battery measurement system with a cut-off voltage range of 3 V to 0.01 V, and the specific capacity was calculated based on the total mass of the active material. The active materials were the SnS2 / RGO nanocomposite prepared in Example 1 and the SnO2 / RGO nanocomposite prepared in Comparative Example 1.

[0092] Figure 5 The SnS2 / RGO composite material prepared in Example 1 was -1 and 2.0 A g -1 Cyclic performance diagram under current density. Figure 5 It can be seen that SnS2 / RGO at 1.0 A g -1 It can stably cycle 250 times at the current density, and the capacity can be maintained at 974.5 mA hg -1 , at 2.0 A g -1 The current density can be stably cycled for 250 cycles, and the capacity can be maintained at 591.6 mA h g -1The above results show that the SnS2 / RGO electrode material prepared by sulfurization induction has excellent cycling performance.

[0093] Figure 6 The figure is the rate performance diagram of SnS2 / RGO prepared in Example 1 and SnO2 / RGO prepared in Comparative Example 1. Figure 6 It can be seen that the rate performance shows that SnS2 / RGO has a good performance in the range of 0.2-10.0 A g -1 The current densities were 936.1, 773.6, 714.9, 648.6, 539.9 and 429.7 mA h g -1 The discharge capacity is restored to 0.2 A g -1 After 105 cycles, the reversible specific capacity can reach 943.3 mA h g -1 The rate performance of SnO2 / RGO is significantly lower than that of SnS2 / RGO, especially at 2.0, 5.0 and 10.0 A g -1 At the current density, the discharge specific capacity provided by SnO2 / RGO is 481.1, 292.1 and 153.4 mA h g -1 The above results show that the ultrafine nanoparticle structure induced by sulfurization and the graphene coating structure significantly enhance the high-rate cycling stability of the electrode material. Figure 5 The mid-cycle performance is consistent.

[0094] Figure 7 The high rate and long cycle performance of the SnS2 / RGO composite material prepared in Example 1 is shown in FIG. Figure 7 It can be seen that SnS2 / RGO at 5.0 A g -1 The current density can be stably cycled for 1100 times, and the capacity can be maintained at 348.9 mA h g -1 The results show that the SnS2 / RGO electrode material prepared by sulfurization induction has excellent electrochemical properties, and its graphene coating structure and nano-modified hybrid structure can significantly improve the high-rate and long-cycle performance of the electrode material.

[0095] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. An application of a graphene-coated tin disulfide nanomaterial as a negative electrode material for a lithium-ion battery in improving the rate performance and cycle performance of a lithium-ion battery, characterized in that: The graphene-coated tin disulfide nanomaterial is prepared by the following method: (1) dispersing graphene oxide in anhydrous ethylenediamine, and then adding tin salt and ultrasonically dispersing to obtain a dispersion; (2) Adding NaOH solution dropwise to the dispersion, stirring to react, centrifuging, washing, and freeze-drying the reactant to obtain Sn6O4(OH)4 / GO; (3) Sn6O4(OH)4 / GO and sublimed sulfur are calcined at high temperature under an inert atmosphere to obtain SnS2 / RGO with an average particle size of 2-5 nm.

2. The use according to claim 1, characterized in that: In step (1), the ratio of the added amounts of graphene oxide, anhydrous ethylenediamine and tin salt is (30-50) mg: (20-40) mL: (200-500) mg.

3. The use according to claim 1, characterized in that: In step (1), the tin salt is one or more of SnCl4·5H2O and SnCl2·2H2O.

4. The use according to claim 1, characterized in that: The concentration of the NaOH solution is 0.12-0.15 mol / L, and the volume ratio of the NaOH solution to anhydrous ethylenediamine is (0.5-1.5): (0.5-1.5).

5. The use according to claim 1, characterized in that: In step (2), the reaction time is 40-100 min.

6. The use according to claim 1, characterized in that: In step (3), the mass ratio of Sn6O4(OH)4 / GO and sublimated sulfur is 1:(1-3).

7. The use according to claim 1, characterized in that: In step (3), the high temperature calcination conditions are: heating to 400-600°C at a heating rate of 2-5°C / min, and maintaining the temperature for 0.5-1.5h.

8. The use according to claim 1, characterized in that: In step (1), the graphene oxide is prepared by the following method: Graphite powder, sulfuric acid with a mass concentration of 98% and sodium nitrate are ultrasonically dispersed uniformly to obtain a mixture; potassium permanganate is added to the mixture, stirred uniformly, and then deionized water and 30% hydrogen peroxide are added dropwise, followed by stirring for 50-70 hours. The obtained brown mixture is washed and centrifuged to obtain graphene oxide.

9. The use according to claim 8, characterized in that: The ratio of the added amounts of graphite powder, concentrated sulfuric acid, sodium nitrate, potassium permanganate, deionized water and hydrogen peroxide is: (4-6) g: (100-140) ml: (2-3) g: (10-20) g: (100-200) ml: (25-75) ml.

Citation Information

Patent Citations

  • Tin sulfide / graphene sodium ion battery composite cathode material and preparation method thereof

    CN106654192A

  • Preparation method of 3D honeycomb-like reduced grapheme oxide tin disulfide compound

    CN107134574A

  • Preparation method and application of double transition metal sulfide composite material coated with reduced graphene oxide

    CN117766711A

Cited By

  • Preparation method of chitosan-induced SnS2 nitrogen-doped carbon negative electrode material and application

    CN122930811A